Standard Audit File for Tax – SAF-T - Elena STĂNCIULESCU (CECCAR Business Review)

(untitled)
Considering the role of SAF-T Standard Audit File for Tax (D406) in terms of taxpayers’ relation with the National Agency of Fiscal Administration and the fact that, starting with January 1, 2025, a significant category of taxpayers will be required to submit the D406 informative statement, by this article we aim to present the categories of taxpayers who must submit the SAF-T file, those who are not required to submit the statement, and the structure of this file. It is also essential to know aspects of consistency tests that can be applied to ensure compliance upon submittal. The Standard Audit File for Tax represents a means of evidence, being an additional reason to be aware of the importance of declaring correct information that reflects reality.